2021
DOI: 10.1108/jabs-10-2020-0415
|View full text |Cite
|
Sign up to set email alerts
|

Digital transformations and supply chain management: a Lean Six Sigma perspective

Abstract: Purpose With the advent of technological connectivity and access to massive data, the possibilities of augmenting Lean Six Sigma’s Define-Measure-Analyze-Improve-Control (LSS’s DMAIC) problem-solving approach with advanced technologies are enormous. This paper aims to examine digital transformations (DT) of supply chains from a process improvement angle using the LSS DMAIC approach. Design/methodology/approach This paper uses a case study approach. Three exemplary case studies were examined to shed light on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Privacy and security must be protected throughout the digital supply chain [53,56]. Elevate and involve customers to raise expectations and deliver value [41,42,43,44,52,54,56,71].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Privacy and security must be protected throughout the digital supply chain [53,56]. Elevate and involve customers to raise expectations and deliver value [41,42,43,44,52,54,56,71].…”
Section: Discussionmentioning
confidence: 99%
“…Quality improvement benefits include faster execution, quality control, defect identification, customer acceptance, staff satisfaction, timely data, waste reduction and more [37,39,40,41]. Value orientation focuses on the customer, driving improvements in performance, productivity and requires the ability to estimate appropriate levels of effort [33,39,42,43,44,45]. Outcomes are more predictable with conventional tools [46].…”
Section: Optimization and Benefitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research indicated gaps in literature both empirically and theoretically concerning the impacts of COVID-19 pandemic on SCs and SC sustainability under the pandemic (Chowdhury et al , 2021; Settembre Blundo et al , 2019), the impacts of the pandemic in the waste supply chain (Appolloni et al , 2021) and in other industrial sectors (Paul and Chowdhury, 2020). Concurrently, other studies underlined the need for considering eco-innovation practices for overcoming the sustainability issues triggered by CODIV-19 in India (Marimuthu et al , 2021) and furthermore, how problem-solving approaches (such as lean six sigma’s define-measure-analyze-improve-control) could improve the practical application of SCs (Settembre Blundo et al , 2019; Tay and Loh, 2021).…”
Section: Introductionmentioning
confidence: 99%